Diagnóstico financiero y análisis del capital de trabajo en la compañía Loja System C. A, periodo 2010 - 2011 - Rueda Pucha, Valeria Tatiana (2016)
The thesis called "FINANCIAL DIAGNOSIS AND ANALYSIS OF WORKING CAPITAL IN THE COMPANY LOJASYSTEM CA, period 2010 -2011.", Developing it to meet its economic and financial situation, and as stipulated in the regulations of Academic Regime the National University of Loja, prior to choose the degree of Engineer in Accounting and Auditing, Auditor CPA requirement. The first specific objective is to implement Financial Indices for determining the liquidity, profitability, indebtedness, where he obtained a current ratio of 6.94 (2010) and 4.29 in 2011, a 1.4 inventory turnover times 2010 every 257 days and 1.62 times in 2011 every 222 days; the return on equity 1.8% in 2010 and 8.5% in 2011 and finally a debt ratio of 14% in 2010 and 23% in 2011; where the company demonstrates a moderate economic-financial situation. The second objective is to evaluate the structure of working capital to determine their quality, with which the company can set the use of financial resources; after canceling its current obligations in 2010 is $ 117,054.08 and 104,889.34 in 2011 that allows meet their needs. The third specific objective is to break even applied to determine the minimum level of income to determine and know that operations must 6 maintain to cover all its costs and expenses; for the period 2010 to maintain income 206,106.38 and the installed capacity will be of 59% for 2011 was 87% capacity and income of 230,346.92. The fourth specific objective is to make the proper diagnosis of the financial report and analysis of working capital as to show the economic and financial situation of the Company LojaSystem CA. The thesis is aimed at providing support for the business owner to timely decision-making and for the fulfillment of these objectives has been used various methods which can point to the same scientific method that was present throughout allowing development work to know how to get the problem under investigation, and made it possible to develop the Financial Diagnosis and presentation of report; inductive and deductive method allowed for the literature review to point out weak areas of the company concluding with the determination of the problem under study and focus in general to the development and operation business to publicize the findings by the phenomena found to generate Possible recommendations for the company. Including the implementation of financial indicators to measure liquidity, activity, profitability, leverage and analyze working capital, enabling the owner to know the profitability of the company, legality and accuracy, 7 which will be beneficial to the owner in the making appropriate decisions within the company.